1980
DOI: 10.1111/j.1600-0447.1980.tb00595.x
|View full text |Cite
|
Sign up to set email alerts
|

A model of the functional psychoses

Abstract: A model of the functional psychoses is described which accounts for their existence, answers certain questions about them and generates refutable predictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1986
1986
1986
1986

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Of the many research methods available to study depression, the information-processing approach has the advantage of being experimental, non-invasive, objective, quantitative and reliable (see Teuting (1981) for a review of current research on depression). At least two theories postulate that depression primarily involves a sensory information processing deficit (Johnson, 1975;Nunn, 1980). Consistent with this view are the results of two studies in which some depressed patients are reported to be less sensitive to visual flicker than other patients and normal controls (Black et al 1975;Perris, 1966).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Of the many research methods available to study depression, the information-processing approach has the advantage of being experimental, non-invasive, objective, quantitative and reliable (see Teuting (1981) for a review of current research on depression). At least two theories postulate that depression primarily involves a sensory information processing deficit (Johnson, 1975;Nunn, 1980). Consistent with this view are the results of two studies in which some depressed patients are reported to be less sensitive to visual flicker than other patients and normal controls (Black et al 1975;Perris, 1966).…”
Section: Introductionmentioning
confidence: 92%
“…It is not clear whether depressed patients exhibit the type of sensory processing deficits described by Johnson (1975) and Nunn (1980), or whether they are simply more reluctant to respond 'flicker' (i.e. are more conservative).…”
Section: Introductionmentioning
confidence: 99%